2004
DOI: 10.1521/psyc.67.3.294.48985
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up after Inpatient Psychiatric Hospitalization with Partial Control of the System Responsiveness Variable

Abstract: One of the most significant predictors of prompt rehospitalization following psychiatric hospital discharge is missing follow-up out-patient appointments. Previous studies have suggested that system responsiveness accounted for much of the variance in predicting compliance with aftercare. Collaborations established at our institution allowed us to partially control this variable, opening the way to explore other obstacles to aftercare. All severely mentally ill subjects discharged from our hospital are provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Studies of psychiatric samples (i.e. samples of individuals who are identified in mental health settings and have some form of SMI) have found that comorbid substance abuse is one of the strongest factors associated with noninitiation and nonengagement in mental health treatment (El-Mallakh et al, 2004; Fischer et al, 2008; see Kreyenbuhl, Nossel, & Dixon, 2009 and O'Brien, Fahmy, & Singh, 2009 for reviews). Factors related to the context of treatment, including dissatisfaction with care and service providers, have been reported by individuals with SMI as reasons for nonengagement or disengagement in mental health treatment (see Kreyenbuhl, Nossel, & Dixon, 2009 and O'Brien, Fahmy, & Singh, 2009 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of psychiatric samples (i.e. samples of individuals who are identified in mental health settings and have some form of SMI) have found that comorbid substance abuse is one of the strongest factors associated with noninitiation and nonengagement in mental health treatment (El-Mallakh et al, 2004; Fischer et al, 2008; see Kreyenbuhl, Nossel, & Dixon, 2009 and O'Brien, Fahmy, & Singh, 2009 for reviews). Factors related to the context of treatment, including dissatisfaction with care and service providers, have been reported by individuals with SMI as reasons for nonengagement or disengagement in mental health treatment (see Kreyenbuhl, Nossel, & Dixon, 2009 and O'Brien, Fahmy, & Singh, 2009 for reviews).…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that starting substance abuse treatment is particularly challenging among dual diagnosis patients (reviewed in Brown and colleagues 15,[28][29][30]. Prior studies have shown that dual diagnosis patients with psychotic spectrum disorders have an even greater challenge in successful treatment initiation.…”
Section: Addictive Disorders and Their Treatmentmentioning
confidence: 99%
“…Increasing the percentage of follow-up after hospital discharge is a critical step to enhance treatment prognosis for people with mental illness and/or addictions (El-Mallakh et al, 2004;Byers & Cohen, 1979;Solomon, Davis, & Gordon 1984;Winston, Pardes, Papernick, & Breslin, 1977). A United States study revealed 50 % t to 60 % initial follow-up after hospital discharge with a range of 13% to 90% (ElMallakh et al, 2004).…”
Section: Post Acute Follow-up Considerationsmentioning
confidence: 99%
“…They found that the variables or predictors related to follow-up compliance include client vulnerability, community support or system responsiveness (El-Mallakh et al, 2004). Of these three predictors, system responsiveness (convenience of scheduling and proximity of location) is cited more frequently than vulnerability of individual and community support as a barrier to follow-up (Klinkenberg & Calsyn, 1996).…”
Section: Post Acute Follow-up Considerationsmentioning
confidence: 99%
See 1 more Smart Citation